The Impact of Client Status on Street-Level Bureaucrats' Identity and Informal Accountability. (4th March 2019) - Pivoras, Saulius; Kaselis, Mindaugas
Abstract : Combining assumptions from the theory of street-level bureaucracy, sociological theory of identity, and grid-group cultural theory, this article first provides an analytical model and typology of administrative identities of frontline public servants. Then qualitative data analysis is done by drawing upon the observations and interview conducted at the State Tax Inspectorate and the Social Security agencies in Lithuania. Research data show that weak discretion does not narrow the variety of administrative identities. Manifestation of informal accountability of street-level bureaucrats to an individual citizen-client as a constitutive part of an administrative identity most clearly appears in interaction with those clients who are considered socially vulnerable. Informal accountability to citizen-clients is especially limited when it is combined with other identity attitudes, such as rigid manner of rule application and limited empathy toward citizen-clients.